Evolving Dynamics of Fermented Food Microbiota and the Gut Microenvironment: Strategic Pathways to Enhance Human Health - Terpou, Antonia; Dahiya, Divakar; Nigam, Poonam Singh (Foods, 2025)
The growing interest in health-promoting diets has brought fermented foods into the spotlight due to their unique microbial compositions and bioactive metabolites. Fermented foods and their beneficial microbiota are expected to stimulate the overall industry’s expansion over the next few years as their beneficial health effects become established. This narrative review explores the evolving dynamics of fermented food microbiota and their interactions with the gut microenvironment, emphasizing strategic pathways to enhance human health. Fermented foods, both industrially produced and traditionally prepared, serve as carriers of beneficial microorganisms such as lactic acid bacteria, yeasts, and certain fungi that transform food substrates into bioactive compounds including short-chain fatty acids (SCFAs), exopolysaccharides, and bioactive peptides. Simultaneously, their bioactive metabolites are the subject of passionate investigation by the scientific community, uncovering novel beneficial aspects that have not been elucidated until now. These metabolites contribute to improved gut barrier function, modulation of immune responses, and overall metabolic health. Notably, microbial fermentation can reshape the intrinsic properties of food, offering therapeutic potential beyond basic nutrition. The interactions between food-derived microbes and the host gut microbiota suggest a synergistic mechanism influencing gastrointestinal and systemic health outcomes. Nevertheless, there remains a significant gap in the comprehensive evaluation of the existing literature in this specific research area. Further research is needed to standardize fermented food formulations, validate the effects of individual microbial strains, and optimize their application in personalized nutrition and functional food development. Accordingly, this review highlights the association between the microbiota of fermented foods and their metabolites with the gut microenvironment, emphasizing their potential health-promoting properties.